Travels of a Genre : The Modern Novel and Ideology - Layoun, Mary N. (Book collections on Project MUSE., 2014)
If the modern Western novel is linked to the rise of a literate bourgeoisie with particular social values and narrative expectations, to what extent can that history of the novel be anticipated in non-Western contexts? In this bold, insightful work Mary Layoun investigates the development of literary practice in the Greek, Arabic, and Japanese cultures, which initially considered the novel a foreign genre, a cultural accoutrement of ""Western"" influence. Offering a textual and contextual analysis of six novels representing early twentieth-century and contemporary literary fiction in these